Narrating intersectional perspectives across social scales: voicing Valerie - Thimm, Viola (Routledge, Taylor & Francis Group, 2022)
"This book presents a guide to researching intersectionality. Clear and jargon-free, this book introduces a narrative-driven, scalar, and polyvocal approach to the antiracist-feminist framework. Thimm shows students how intersectionality can be used as a methodology, especially in the analysis of multiple 'identities'. This text considers complex social inequalities as parallel to one another - not only gender, race, and class, but also ethnicity, sibling seniority, religion, or educational attainment. Readers will learn how to investigate, in a methodologically structured way, the interwoven realities of life for different people and population groups simultaneously permeated by marginalization and dominance. With multiple-social-scale analysis and deep discussion of how to conduct data collection, evaluation, and write-up, this book will be of interest to students, early-career scholars, and faculties teaching undergraduate and graduate courses in women's, gender, queer, and ethnic studies. Courses in sociology, anthropology, political science and, beyond that, engaged research on how people are marginalized or privileged given their axes of identification, will also find the book an invaluable resource"--
Includes bibliographical references and index
Keywords: Soziale Identität; Lebensbedingungen; Frau; Südostasien